The unlawfulness of the African National Congress' cadre deployment policy in its affect on an efficient administration: is an administration loyal to the ANC compromising service delivery in South Africa? - Stein, Ruth Emily (Department of Public Law, 2026)
This minor dissertation aims to understand the African National Congress' policy of cadre deployment, how this policy impacts on the efficiency of the South African public administration, and whether it sufficiently complies with the Constitution and the relevant law. Particular attention is given to the provision of services in postapartheid South Africa and how the appointment of cadres impacts on improved service delivery. Further attention is placed on the constitutional and legislative mechanisms that protect the ANC government from being held accountable for their decisions to appoint and remove public servants. The transformative and representative nature of the cadre deployment policy is commended. In contrast, the deployment of cadres over candidates better skilled for the job is critiqued in its impact on mismanagement and instability in the administration. The analysis applies the constitutional and legislative provisions promoting an efficient administration to the outcomes of the cadre deployment policy. Evidence on the workings of the cadre deployment policy is put forward through ANC Deployment Committee policies, findings from the Judicial Commission of Inquiry into State Capture, and reports of the Auditor-General. The analysis points to the susceptibility of the policy to private influence. Furthermore, it is evidenced that the policy's preference for party loyalists over persons most fit for purpose leads to mismanagement and instability in the administration. As a result, the efficiency of the administration is compromised by the ANC's cadre deployment policy. This is not to argue, however, that the policy should be abolished. It should, however, be reconsidered to focus more on the qualifications of cadres for the position to which they are appointed, continued training, and effective disciplinary measures for administrators who transgress the law.